EFFECT OF INNOPROVET PROBIOTIC ON THE ORGANISM OF CHICKENS VACCINATED AGAINST LOW-PATHOGENIC AVIAN INFLUENZA - Nazarovich, Axmedov Baxodir; Uktamovich, Murodov Xurshid; o‘g‘li, Sherqulov A’zam Mirzoqul (Research Focus International Scientific Journal, 2026)
The article provides information on the study of effective immunoprophylaxis against avian influenza disease through vaccination with the low-pathogenic avian influenza vaccine Gallimune H9+ND in Loman Brown chickens raised in industrial poultry farms and private farms, together with the use of the Innoprovet probiotic. After vaccination and application of Innoprovet, blood samples were taken from all chickens on days 7 and 14, and their immune status was assessed using the HI test (hemagglutination inhibition reaction). In the experimental groups, a significant increase in antihemagglutinin (antibody) titers was found compared to the control group. Stable and high maintenance of antibody titers on the 14th day of the study showed that chickens developed strong and long-lasting immunity. It was also found that live weight gain in the experimental group was consistently higher than in the control group.